Теоретико-методологічний концепт інституційних трансформацій на міжнародних і національних ринках криптовалют - Белінська, Яніна Василівна; Коваленко, Юлія Михайлівна; Вергелюк, Юлія Юріївна; Белінська, Яніна (Національний університет "Чернігівська політехніка", 2023)
Криптовалюти вже довели свою ефективність і перспективність, тож більшість держав почали формувати нормативно-правову базу щодо їх обігу. Однобоке розуміння криптовалюти з погляду технічної моделі її функціонування не дозволяє розкрити її сутність з погляду економічної науки, що гальмує формування адекватного інституційного забезпечення процедури емісії та обігу криптовалют загалом. Визначено сутність інституцій ринку криптовалют як системи, що включає офіційні (тверді) обмеження (правила), неофіційні (м’які) обмеження (стандарти поведінки та стереотипи мислення) та інтуїцію, які забезпечують досягнення оптимальної організації, координації і стимулювання поведінки учасників (постачальників послуг, пов’язаних з оборотом криптовалют, а також будь-яких осіб, які здійснюють операції з криптовалютами у своїх інтересах) і приводить до скорочення трансакційних витрат. Наведено понятійно-методологічну модель інституцій ринків криптовалют. Розроблено новітні підходи щодо процесу інституційних трансформацій на ринках криптовалют, запропоновано критерії їх інституціалізації. Визначено складові інституційних трансформацій на ринку криптовалют в Україні.

A one-sided understanding of cryptocurrency in terms of the technical model of its functioning does not allow to reveal its essence from the point of view of economic science, which hinders the for-mation of adequate institutional support for the procedure of issuance and circulation of cryptocurren-cies in general. The author defines the essence of cryptocurrency market institutions as a system which includes official (hard) restrictions (rules), unofficial (soft) restrictions (standards of behavior and ste-reotypes of thinking) and intuition, which ensure the achievement of optimal organization, coordination and stimulation of participants' behavior and lead to a reduction in transaction costs. The institutionalization of cryptocurrency markets implies that changes in hard restrictions (reg-ulations) do not simply lead to evasion or adaptation to their implementation by their participants. Institutional transformations in cryptocurrency markets are the process of formation and development of their participating institutions and other entities that implement their inherent institutions in financial transactions with cryptocurrencies; regulation of this activity through official (hard) restrictions on fi-nancial behavior with enforcement mechanisms in the presence of unofficial (soft) restrictions. The main components of institutional transformations in the cryptocurrency market in Ukraine are the importation of institutions and institutional transformations that can lead to institutional traps and congruence/con-vergence of these institutions.As for the theories (concepts) in the field of cryptocurrency markets, many years of experience show that their implementation requires a long time to grow and root the relevant institutions in the mass consciousness for a certain set of ideal procedures. If successful, such theories become effective tools for cryptocurrency operations. The strategy of institutional reform of cryptocurrency markets should be systemic, i.e., along with economic transformations, shifts in morality, social and individual consciousness, etc. must be taken into account.
Keywords: криптовалюта; національні та міжнародні ринки криптовалют; інституція; інституціалізація; інституційні трансформації; cryptocurrency; institution; institu-tionalization; institutional transformations